Fishers ICTs use for early warning reception, it’s effect on Livelihood Resilience and sustainability in East Coast Malaysia - Garba, Bashir Muktar; Man, Norsida; Kamarulzaman, Nitty Hirawaty; Abu Samah, Asnarulkhadi; Umar, Sulaiman (International Organization of Scientific Research, 2018)
Climate change is posing a serious threat to agriculture and hence food security of nations. Achieving sustainable development goals (SDGs) is thus contingent on adaptation measures that are aimed to reduce vulnerability and build resilience. The ICTs are recognized for strengthening Livelihood Resilience (LR), by providing the necessary support for learning process, flexibility in operations or actions and robustness for continued functionality. Yet, empirical literature is scarce on the effect it has on LR, The research while filling this gap, claims initial application of Protective Motivation Theory to assess the effect of ICTs on LR of agricultural communities like Fisher Folks in Malaysia. Findings reveals Social networking as the main reason for use of ICTs by fisher folks, while early warning dissemination is always channelled through radio with other ICTs complementing. The Multiple Regression revealed additional source of income, threat appraisals (perceived vulnerable and severity of flood), coping appraisal of (self-efficacy) to be key determinants of adaptive behaviour and hence are precursor for LR. Thus it can be said that both ICTs Use and PMT constructs affect the LR, suggesting a focus on innovative use of ICTs for adaptation motivation in flood risk reduction communication.